Pengaruh Media Digital Flipbook Terhadap Peningkatan Hasil Belajar Bahasa Indonesia Siswa di Sekolah Dasar - Wulan Dwi Septiani; Tri Linggo Wati (Prodi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze the effect of using digital flipbook media on improving the Indonesia Language learning outcomes of third-grade students at SDN Sudimoro in the 2025/2026 academic year. This study used a quantitative approach with a one group pretest- posttest pre experimental design. The research subjects were given a pretest before the treatment and a posttest after the application of the digital flipbook media. Data collection was conducted through learning outcome test, then analyzed using a paired t-test. The analysis results showed that the average pretest score of 51 increased to 88.33 on the posttest. The paired t-test value obtained was t=12.322 with Sig. (2-tailed) = 0.000 ( < 0,05), indicating a significant difference between the scores before and after the treatment. Based on these findings, it can be concluded that the use of flipbook digital media has a significant effect on improving Indonesia Language learning outcomes in SPOK material for third- grade student. In short, this this media is effective in helping student understand, apply, and analyze sentence structure more systematically.